A Practical Indoor Mobility Course to Assess the Functional Effect of Tunnel Vision - Alshaghthrah, Ali M.; Dickinson, Chris M. (Scandinavian Journal of Optometry and Visual Science, 2014)
Purpose To design and validate an indoor mobility course that is sensitive and easy to assemble in a variety of settings. Method Seventy participants were asked to walk twice along a 14 metre indoor corridor containing 16 obstacles, once in each direction. Twenty participants suffered from varying degrees of tunnel vision (TV) due to retinitis pigmentosa (TVPs) and the TV was simulated in the remaining fifty normally-sighted participants (SIPs).The VA, CS and VF were measured. The binocular field of view (FoV) of the TVPs varied from 4° to 21o. The FoV of the SIPs was constricted using goggles and ranged from 4° to 22°. The SIPs repeated the test at a second visit. In each case the time taken to complete the test was expressed as the percentage preferred walking speed (PPWS) and the number of collisions was recorded. Results For the SIPs, the PPWS and the collision scores both showed a significant relationship to FoV on both visits; for PPWS: r = 0.58; r = 0.56; p <0.0001, respectively; for collisions: r = -0.50, r = -0.55, p < 0.0001, respectively. Generally, no significant difference was found between the mobility scores between visits. The FoV of the TVPs was significantly related to their PPWS scores, r = 0.40, p = 0.04. No relationship was found between the TVPs FoV and collision scores. A significant relationship was found between the TVPs’ VA and collisions (r = 0.40, p = 0.03). There was also a moderate but not significant relationship between the TVPs’ CS and collisions. Conclusion This mobility course is relatively short and does not require dedicated space, so could be easily replicated in other studies. The results indicate that this design is valid and that the course is a useful tool for assessing functional performance in tunnel vision patients.